Negative outcomes of ICT use at work : meta-analytic evidence and the role of job autonomy - Karimikia, Hadi (2021)
Individuals can improve their task performance by using information and communications technology (ICT). However, individuals who use ICT may also suffer from negative outcomes, such as burnout and anxiety, which lead to poorer performance and well-being. While re-searchers have studied the positive outcomes of ICT use in the aggregate, the same has not been done for negative outcomes. This study uses a meta-analysis to examine the relationship between ICT use and negative outcomes, and the influence of job autonomy, or the level of dis-cretion an individual has in conducting his/her job, on ICT use and the negative outcomes of ICT use. Job autonomy is relevant because a higher level of job autonomy allows individuals to decide how, how often, and when they will use ICT that is causing negative outcomes for their work. The results of the meta-analysis revealed that ICT use increased negative job outcomes and that, unexpectedly, autonomy exacerbated this effect. The paper concludes with a discus-sion of the possible reasons for this finding and suggestions for future research.